Increasing Quit Attempts by Transitioning to Very Low Nicotine Content Cigarettes Versus Reducing Number of Cigarettes Per Day: A Secondary Analysis of an Exploratory Randomized Trial. (23rd December 2019) - Klemperer, Elias M; Hughes, John R; Callas, Peter W
Abstract: Introduction: The Food and Drug Administration (FDA) has proposed reducing nicotine with very low nicotine content (VLNC) cigarettes. In contrast, reducing nicotine by reducing number of cigarettes per day (CPD) is common. Our prior findings demonstrate that VLNC cigarettes decreased dependence more and were more acceptable than reducing CPD. This secondary analysis explored which reduction strategy increased quit attempts (QA), self-efficacy, or intention to quit more. Methods: This is a secondary analysis of 68 adult daily smokers not ready to quit randomized to smoke VLNC cigarettes versus reduce CPD over 5 weeks. All participants smoked study cigarettes with nicotine yield similar to most commercial cigarettes ad lib for 1 week (baseline). Participants were then randomized to gradually reduce to 70%, 35%, 15%, and 3% of baseline nicotine over 4 weeks by either (1) transitioning to lower nicotine VLNC cigarettes or (2) reducing the number of full nicotine CPD. All participants received nicotine patches to aid reduction. We assessed (1) QAs using nightly and weekly self-reports, (2) Velicer's Self-Efficacy to Quit measure weekly, and (3) the Intention-to-Quit Ladder nightly. Results: More CPD (41%) than VLNC (17%) participants made any QA (odds ratio = 3.4, 95% confidence interval = 1.1, 10.5). There was no difference in QAs ≥24 h. Self-efficacy increased for VLNC but not CPD participants (interaction: F = 3.7, p < .01). The condition by time interaction for intention-to-quit was not significant. Conclusions: Reducing number of CPD increased QAs more than reducing nicotine via switching to VLNC cigarettes. The lack of difference in longer QAs suggests replication tests are needed. Implications: Reducing the frequency of smoking behavior (ie, CPD) could be a more effective strategy to increase QAs than reducing the magnitude of nicotine in each cigarette (ie, VLNC) per se.